2018
DOI: 10.1172/jci.insight.96836
|View full text |Cite
|
Sign up to set email alerts
|

Immune reprogramming via PD-1 inhibition enhances early-stage lung cancer survival

Abstract: Success of immune checkpoint inhibitors in advanced non-small-cell lung cancer (NSCLC) has invigorated their use in the neoadjuvant setting for early-stage disease. However, the cellular and molecular mechanisms of the early immune responses to therapy remain poorly understood. Through an integrated analysis of early-stage NSCLC patients and a Kras mutant mouse model, we show a prevalent programmed cell death 1/programmed cell death 1 ligand 1 (PD-1/PD-L1) axis exemplified by increased intratumoral PD-1+ T cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
52
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(57 citation statements)
references
References 60 publications
2
52
0
Order By: Relevance
“…The requirement of functional systemic immunity has been previously demonstrated in murine models for the efficacy of other immunotherapy approaches (Spitzer et al , ), as well as the importance of CD4 T cells for anti‐PD‐1 immunotherapy (Markowitz et al , ). These studies are in agreement with our present data in human patients undergoing PD‐L1/PD‐1 blockade therapies.…”
Section: Discussionmentioning
confidence: 95%
“…The requirement of functional systemic immunity has been previously demonstrated in murine models for the efficacy of other immunotherapy approaches (Spitzer et al , ), as well as the importance of CD4 T cells for anti‐PD‐1 immunotherapy (Markowitz et al , ). These studies are in agreement with our present data in human patients undergoing PD‐L1/PD‐1 blockade therapies.…”
Section: Discussionmentioning
confidence: 95%
“…Next, we performed gene-set enrichment analysis (GSEA) on published bulk RNA-seq data of CD8 TILs following anti-PD-1 therapy (raw data in murine sarcoma from (Gubin et al, 2014). Our results indicated that ICB led to a selective enrichment of the EM-like signature (p=0.035, Figure 6 A, raw data from (Markowitz et al, 2018)).…”
Section: Pd-1 Checkpoint Blockade Expands Em-like Cellsmentioning
confidence: 97%
“…RNA-seq data of CD8 TILs in murine sarcoma (tumors were harvested at day 12 post-transplant, 3 days after treatment) was obtained from GEO accession GSE62771 (anti-PD-1 vs control) (Gubin et al, 2014). RNA-seq data of CD8 TILs in non-small cell lung cancer (anti-PD1 vs control) were obtained from GEO accession GSE114300 (Markowitz et al, 2018). RNA-seq data from adoptively transferred (in vitro activated) OT-1 cells infiltrating B16-OVA tumors (anti-PD1 vs control) were obtained from GEO GSE93014 (Mognol et al, 2017).…”
Section: Gene Signature Analysismentioning
confidence: 99%
“…In the past decade, and while exploration of the immune landscape of PMLs was still in its infancy, immunotherapy was tested in early stage lung tumors with promising results (245,246). Interestingly, early-stage LUADs treated with standard adjuvant therapy exhibited mutations in genes involved in immune regulation that are also associated with smoking (211).…”
Section: Immuno-adjuvant and Neoadjuvant Therapy In Early Stage Lung mentioning
confidence: 99%